HUBUNGAN ASUPAN GIZI DAN KONSUMSI ROKOK DENGAN KADAR HEMOGLOBIN PADA REMAJA LAKI-LAKI USIA 15-18 TAHUN DI KELURAHANWEK I KECAMATAN PADANGSIDIMPUAN UTARA - EKA PUTRI R RANGKUTI; Ernawati Nasution; Zulhaida Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Haemoglobin is one of the compounds in red blood cells that function to transport oxygen into the cells of the body. Haemoglobin levels are used as the parameters determining status of anemia. Anemia is a condition in which the number of red blood cells or haemoglobin levels in the blood is less than normal. Causes of anemia can be various, such as lack of iron levels in the body, deficiency of folic acid, vitamin B12 deficiency, and so on. Adolescent age group is a phase of rapid growth so that at this time required a relatively larger amount of nutrients.This type of research was an analytical survey with cross sectional design. The population in this research were all adolescent boys aged 15-18 years who lived in Kelurahan Wek I, Kecamatan Padangsidimpuan Utara, sample was taken from 70 of 213 adolescent boys and taken by simple random sampling. Data obtained from the 24 hours recall form results to determine the nutrient intake and used the questionnaire sheet on the consumption of cigarettes, and by checking the blood directly used easy touch to determine the level of Hb in adolescents. Data analysis used chi-square test with a confidence level of 95 %.Research results obtained the levels of Hb <12 g/dl (anemia) on adolescent boys in Kelurahan Wek I, Kecamatan Padangsidimpuan Utara was 38,6%. The results of the analysis showed three variables that have a significant relationship with Hb levels in adolescents ie energy p = 0,029, Fe p = 0,022 and vitamin B12 p = 0,036.Expected to thelocalPuskesmas  to do counseling to the community especially the adolescent boys about the dangers of smoking and the importance of increasing the consumption ofnutritious foods to meet nutritional intake and reduce the numbers ofanemia in adolescents. Keywords :      Haemoglobin Levels, Nutrient Intake, Cigarettes Consumption, Adolescent Boy